Three-dimensional cross-linking channeling sealing technology based on electrostatic force

Through electrostatic three-dimensional crosslinking technology, the use of positive electrocoupling copolymers to produce chemical adsorption with the rock surface, solving the problems of fast glue formation speed and poor erosion resistance in the existing technology, and achieving effective sealing and long-term sealing of the high-permeability layer Stability improves the recovery rate and erosion resistance of the reservoir.

CN119286485APending Publication Date: 2025-01-10HAINAN GELAN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411398224.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing sealing technology has fast glue formation speed and poor erosion resistance under strong water oil reservoir conditions, making it difficult to ensure the long-term effectiveness of the adjustment of the profile and drive measures.

Method used

Using the three-dimensional cross-linking and trashing technology based on electrostatic force, using positive electroplastic copolymers with a large amount of positive charges, chemical adsorption is generated with the rock surface through cationic cross-linking agents to form a cement with a high permeability layer, reducing the permeability of the water phase And improve the water absorption profile.

Benefits of technology

The firm adsorption of the cemented body on the rock surface is achieved, the water phase permeability of the high permeability zone is reduced, the effect of the water absorption profile is improved, and the recovery rate and erosion resistance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286485A_ABST
    Figure CN119286485A_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional cross-linking channeling sealing technology based on electrostatic force, which comprises a cementitious body for sealing, and a mixing method of the cementitious body comprises the following steps: (1) taking 200g as an example, weighing 198.44 g of water, adding 0.4 g of polymer while stirring, and stirring for 2 hours until the polymer is completely dissolved; (2) adding 1 g of cationic cross-linking agent 1 and 1 g of cationic cross-linking agent 2, and uniformly stirring; (3) adding 0.16 g of an auxiliary agent, and stirring until the auxiliary agent is completely dissolved; and (4) putting the prepared solution in an environment of 45 DEG C, and observing the gel forming condition. A cementitious body formed by the electropositive gel copolymer with a large number of positive charges and the electropositive gel plugging adjusting system is adopted, the cementitious body can be firmly adsorbed on the surface of electronegative rock after being injected underground, residual polymers in an underground flow field can be trapped by surplus positive charges, and the plugging adjusting effect is good. The water-phase permeability of the high-permeability zone is gradually reduced, and finally the effects of plugging the high-permeability layer and improving the water absorption profile are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield operation, in particular to a three-dimensional cross-linking sealing technology based on electrostatic force. Background Art

[0002] Under the action of long-term high-intensity water injection and scouring, the sandstone particles of the strong water channeling oil field become very loose and highly hydrophilic on the surface, forming a certain water flow channel in the reservoir. The surface of this water flow channel carries a large amount of negative charge and has obvious directionality, which will cause the rapid and ineffective circulation of the subsequent injected fluid. The water channeling channel of the oil reservoir is washed by water for a long time, making the rock surface negatively charged, and long-term injection and scouring form a high permeability zone. The existing sealing technology has problems such as fast gelation speed and poor scouring resistance under the conditions of strong water channeling oil reservoirs, making it difficult to ensure the long-term effectiveness of the profile adjustment and flooding measures. Summary of the invention

[0003] The purpose of the present invention is to provide a three-dimensional cross-linking sealing technology based on electrostatic force to solve the problems raised in the above background technology.

[0004] In order to achieve the above object, the present invention adopts the following technical scheme: a three-dimensional cross-linking sealing technology based on electrostatic force, including a cementing body for sealing, and the mixing method of the cementing body is as follows:

[0005] (1) Taking 200g as an example, weigh 198.44g of water and add 0.4g of polymer (equivalent to 2000mg / L of polymer) while stirring, and stir for 2 hours until the polymer is completely dissolved;

[0006] (2) Add 1 g of cationic crosslinker 1 and cationic crosslinker 2 (crosslinker equivalent to 5000 mg / L) (cationic crosslinker 1: cationic crosslinker 2 = 1:1 to 5:1), and stir evenly;

[0007] (3) Add 0.16 g of additive (800 mg / L) and stir until completely dissolved;

[0008] (4) Place the prepared solution in a 45°C environment and observe the gelation process.

[0009] Preferably, the synthesis process of the cationic crosslinking agent 1 comprises the following steps:

[0010] (1) After adding a certain amount of acrylamide, acrylic acid, cationic monomer (dimethyldiallyl ammonium chloride DMDAAC / acryloyloxyethyl trimethyl ammonium chloride), dispersant (sodium sulfate), emulsifier (lauryl alcohol polyether), initiator A (ammonium persulfate) and ionized water into a reactor, N2 was introduced and stirred at a speed of 350 r / min to fully mix;

[0011] (2) Raise the temperature to 60°C and slowly drop the initiator B solution. After the addition of initiator B (sodium bisulfite) is complete, stir the reaction at a constant temperature for 4 hours to obtain a uniform liquid, which is then cooled for use.

[0012] Preferably, the synthesis process of the cationic crosslinking agent 2 comprises the following steps:

[0013] (1) Add an appropriate amount of organic solvent (epichlorohydrin) and deionized water into a reaction vessel and stir at a rate of 350 r / min to mix them thoroughly;

[0014] (2) Slowly add raw material A (ethylenediamine) and catalyst B (ammonium persulfate), stir and react at 60°C, add raw material C (acryloyloxyethyltrimethylammonium chloride) dropwise, raise the temperature to 90°C after the addition is complete, keep the temperature for reaction for 3 hours, and then cool to obtain a uniform liquid.

[0015] Preferably, the auxiliary agent is composed of an antibacterial agent dodecylbenzyl ammonium chloride (1227), a gel promoter disodium ethylenediaminetetraacetate (EDTA), and a regulator mainly composed of thiourea.

[0016] Preferably, the polymer is an ultra-high-density (2500×104) salt-resistant polymer and a high-density polymer (1600-1900×104).

[0017] Preferably, the concentration of the auxiliary agent is not higher than 800 mg / L and not lower than 400 mg / L.

[0018] Preferably, the polymer concentration is not higher than 4000 mg / L and not lower than 1000 mg / L.

[0019] Preferably, the concentration of the cross-linking agent is not higher than 5000 mg / L and not lower than 2000 mg / L.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention adopts a positively charged gel copolymer with a large amount of positive charges and positive electrical properties. The gel formed by the positively charged gel plugging system can be firmly adsorbed on the negatively charged rock surface after being injected underground. The surplus positive charge can capture the residual polymer in the underground flow field, gradually reduce the water phase permeability of the high permeability zone, and finally achieve the effect of plugging the high permeability layer and improving the water absorption profile. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic diagram of the research and development route of the three-dimensional cross-linking system of the present invention;

[0023] Figure 2 Schematic diagram of the molecular structure of the cationic crosslinking agent 1 of the present invention;

[0024] Figure 3Schematic diagram of the molecular structure of cationic crosslinking agent 2 of the present invention;

[0025] Figure 4 It is a schematic diagram of the molecular structure of the strong water breakthrough oil reservoir profile control system of the present invention. DETAILED DESCRIPTION

[0026] In order to further explain the technical solution of the present invention, it is described in detail below through specific embodiments.

[0027] See also Figure 1-Figure 4 The present invention provides a three-dimensional cross-linking sealing technology based on electrostatic force, including a cementing body for sealing, and the mixing method of the cementing body is as follows:

[0028] (1) Taking 200g as an example, weigh 198.44g of water and add 0.4g of polymer (equivalent to 2000mg / L of polymer) while stirring, and stir for 2 hours until the polymer is completely dissolved;

[0029] (2) Add 1 g of cationic crosslinker 1 and cationic crosslinker 2 (crosslinker equivalent to 5000 mg / L) (cationic crosslinker 1: cationic crosslinker 2 = 1:1 to 5:1), and stir evenly;

[0030] (3) Add 0.16 g of additive (800 mg / L) and stir until completely dissolved;

[0031] (4) Place the prepared solution in a 45°C environment and observe the gelation process.

[0032] The cationic crosslinking agent 1 of the present invention contains cationic chains that can produce strong chemical adsorption with the negatively charged rock surface, neutralize the charge with the carboxylic acid group of polyacrylamide, and form a gel. It can block the high permeability zone formed by long-term injection and scouring, change the direction of liquid flow in the layer, and achieve the effect of increasing the swept volume of the low permeability layer section near the wellbore.

[0033] The cationic crosslinking agent 2 in the present invention is a promoter, which can promote the hydrolysis and separation of positive charges in the cationic crosslinking agent 1, react with the polymer faster and better, and at the same time make the product more firmly adsorbed on the rock surface, reducing the rock pore radius.

[0034] The synthesis process of cationic crosslinker 1 comprises the following steps:

[0035] (1) After adding a certain amount of acrylamide, acrylic acid, cationic monomer (dimethyldiallyl ammonium chloride DMDAAC / acryloyloxyethyl trimethyl ammonium chloride), dispersant (sodium sulfate), emulsifier (lauryl alcohol polyether), initiator A (ammonium persulfate) and ionized water into a reactor, N2 was introduced and stirred at a speed of 350 r / min to fully mix;

[0036] (2) Raise the temperature to 60°C and slowly drop the initiator B solution. After the addition of initiator B (sodium bisulfite) is complete, stir the reaction at a constant temperature for 4 hours to obtain a uniform liquid, which is then cooled for use.

[0037] The synthesis process of cationic crosslinker 2 comprises the following steps:

[0038] (1) Add an appropriate amount of organic solvent (epichlorohydrin) and deionized water into a reaction vessel and stir at a rate of 350 r / min to mix them thoroughly;

[0039] (2) Slowly add raw material A (ethylenediamine) and catalyst B (ammonium persulfate), stir and react at 60°C, add raw material C (acryloyloxyethyltrimethylammonium chloride) dropwise, raise the temperature to 90°C after the addition is complete, keep the temperature for reaction for 3 hours, and then cool to obtain a uniform liquid.

[0040] The auxiliary agent in the present invention is composed of an antibacterial agent dodecylbenzyl ammonium chloride (1227), a gel promoter disodium ethylenediaminetetraacetic acid (EDTA), and a regulator mainly composed of thiourea. The auxiliary agent concentration is not higher than 800 mg / L and not lower than 400 mg / L. The polymer adopts an ultra-high-density (2500×104) salt-resistant polymer and a high-density polymer (1600-1900×104). The polymer concentration is not higher than 4000 mg / L and not lower than 1000 mg / L. The cross-linking agent concentration is not higher than 5000 mg / L and not lower than 2000 mg / L.

[0041] Formula optimization of electrostatic force three-dimensional cross-linking sealing technology in the present invention

[0042] 1. Optimal concentration of polymerized monomers

[0043] A cationic crosslinking agent was fixedly selected at a concentration of 3000 mg / L, polymer types were KYJ and NT, polymer monomer concentration was changed, reaction temperature was 65°C, and the gel formation conditions of changing polymer concentration were shown in Table 1.

[0044] Table 1 Gel formation by changing polymer concentration

[0045]

[0046] It can be concluded from Table 1 that the gelling viscosity of KYJ is higher than that of NT polymer, and KYJ polymer is recommended. As the polymer concentration increases, the gelling viscosity of the two systems gradually increases. When the polymer concentration exceeds 4000 mg / L, the increase in system viscosity decreases. The recommended polymer concentration is not less than 1000 mg / L and not more than 4000 mg / L.

[0047] 2. Effect of crosslinker concentration

[0048] (1) Cross-linking agent concentration (single factor analysis)

[0049] The polymer KYJ was fixedly selected with concentrations of 2000 mg / L, 3000 mg / L, and 4000 mg / L, respectively. The concentration of the cross-linking agent monomer was changed from 2000 mg / L to 6000 mg / L, and the gelation was observed, as shown in Table 2.

[0050] Table 2 Gel formation by changing crosslinker concentration

[0051]

[0052] It can be concluded from Table 2 that under the condition of a certain polymer concentration, as the cross-linking agent concentration increases, the system viscosity gradually increases and then gradually decreases. When the cross-linking agent concentration is higher than 5000 mg / L, the system viscosity shows a downward trend. Therefore, the recommended cross-linking agent concentration is not higher than 5000 mg / L and not lower than 2000 mg / L.

[0053] (2) Effect of cross-linking agent ratio (single factor analysis)

[0054] The polymer KYJ was fixedly selected at a concentration of 2000 mg / L, and the ratio of cationic crosslinker 1: cationic crosslinker 2 was changed to JL1:JL2=1:1, 3:1, 5:1, and 7:1 respectively. The reaction temperature was 65°C, and the gelation was observed, as shown in Table 3.

[0055] Table 3 Gel formation by changing cross-linking ratio

[0056]

[0057]

[0058] It can be concluded from Table 3 that, under the condition of a certain JL1:JL2 ratio, as the cross-linking agent concentration increases, the system viscosity gradually increases; under the condition of a certain cross-linking agent concentration, as the JL1:JL2 ratio increases, the system viscosity gradually increases, and then gradually decreases in the later period. It is recommended that JL1:JL2 = not more than 7:1.

[0059] 3. Influence of additive concentration

[0060] The polymer KYJ was fixedly selected at a concentration of 2000 mg / L, the cross-linking agent concentration was 2000 mg / L-4000 mg / L, and the auxiliary agent concentration was changed to 400 mg / L, 500 mg / L, 600 mg / L, 700 mg / L, and 800 mg / L, respectively. The reaction temperature was 65°C, and the gelation was observed as shown in Table 4.

[0061] Table 4 Gel formation with changing additive concentration

[0062]

[0063] It can be seen from Table 4 that under the conditions of certain polymer concentration and cross-linking agent concentration, as the additive concentration increases, the system viscosity gradually increases and then decreases. The recommended additive concentration is not higher than 700 mg / L and not lower than 400 mg / L.

[0064] Based on the results of the optimization research on the formula of electrostatic force three-dimensional cross-linking sealing technology, the formula of the strong water channeling reservoir profile control system is as follows:

[0065] High strength gel parameters: ultra high score (2500×10 4 ) Salt-resistant polymer Cp = 3000-4000 mg / L; Cj>4000 mg / L; JL1:JL2 = 3:1-5:1, C additive = 600-700 mg / L.

[0066] Medium strength gel parameters: high polymer (1600-1900×10 4 )Cp=2000~3000mg / L;Cj>3000mg / L;JL1:JL2=1:1~3:1,C auxiliary agent=500~600mg / L.

[0067] In the present invention, a cationic crosslinking agent (composed of a cationic crosslinking agent 1, a cationic crosslinking agent 2 (promoter) and an auxiliary agent) is selected to crosslink with an anionic polymer to generate a profile control agent with positive properties. Wherein the cationic crosslinking agent 1 (JL1) contains cationic links, which can produce strong chemical adsorption with the negatively charged rock surface, neutralize the charge with the carboxylic acid group of polyacrylamide, form a gel, block the high permeability zone formed by long-term injection scouring, change the direction of liquid flow in the layer, and achieve the effect of increasing the swept volume of the low permeability layer section in the near-well zone. Cationic crosslinking agent 2 is a promoter, which can promote the large hydrolysis and separation of positive charges in the cationic crosslinking agent 1, react with the polymer faster and better, and make the product more firmly adsorbed on the rock surface, reduce the rock pore radius, thereby forming a high-strength spatial network structure crosslinking system with multi-point crosslinking, and firmly adsorbed on the negatively charged rock surface, realize the blocking of the large pores of the strong water channeling oil reservoir and thus improve the recovery rate, and the developed profile control system has the characteristics of high strength, scouring resistance and positive charge.

[0068] The formula of the strong water channeling oil reservoir profile control system has the following characteristics: 1. The positively charged amino group in the strong water channeling oil reservoir profile control system can change the electrical properties of the rock (negative to positive), so that the anionic polymers from the injection end and the formation are more adsorbed on the rock surface; 2. The cationic chain segments contained in the strong water channeling oil reservoir profile control system can react with the polyacrylamide in the injection fluid and the carboxylic acid groups of the polyacrylamide retained in the formation to undergo chemical charge neutralization reactions and physical cross-linking reactions to generate three-dimensional network polymers; 3. When the strong water channeling oil reservoir profile control system encounters the water phase, the molecular chains fully stretch and extend to the pores, effectively blocking the pores, reducing the effective radius of the pores, and causing the water phase permeability to decrease; 4. The strong water channeling oil reservoir profile control system that enters the oil flow channel of the reservoir has a curled molecular chain in the oleophilic medium, which has little effect on the effective radius of the pore throat, and flows into the wellbore with the oil flow, so it has little effect on the oil phase permeability, showing good selective water plugging performance.

[0069] The above description is only a preferred example of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A three-dimensional cross-linking sealing technology based on electrostatic force, characterized in that: The invention comprises a cementing body for plugging, wherein the mixing method of the cementing body is as follows: (1) Taking 200g as an example, weigh 198.44g of water and add 0.4g of polymer (equivalent to 2000mg / L of polymer) while stirring, and stir for 2 hours until the polymer is completely dissolved; (2) Add 1 g of cationic crosslinker 1 and cationic crosslinker 2 (crosslinker equivalent to 5000 mg / L) (cationic crosslinker 1: cationic crosslinker 2 = 1:1 to 5:1), and stir evenly; (3) Add 0.16 g of additive (800 mg / L) and stir until completely dissolved; (4) Place the prepared solution in a 45°C environment and observe the gelation process.

2. According to claim 1, a three-dimensional cross-linking sealing technology based on electrostatic force is characterized in that: The synthesis process of the cationic crosslinking agent 1 comprises the following steps: (1) After adding a certain amount of acrylamide, acrylic acid, cationic monomer (dimethyldiallyl ammonium chloride DMDAAC / acryloyloxyethyl trimethyl ammonium chloride), dispersant (sodium sulfate), emulsifier (lauryl alcohol polyether), initiator A (ammonium persulfate) and ionized water into a reactor, N2 was introduced and stirred at a speed of 350 r / min to fully mix; (2) Raise the temperature to 60°C and slowly drop the initiator B solution. After the addition of initiator B (sodium bisulfite) is complete, stir the reaction at a constant temperature for 4 hours to obtain a uniform liquid, which is then cooled for use.

3. According to claim 1, a three-dimensional cross-linking sealing technology based on electrostatic force is characterized in that: The synthesis process of the cationic crosslinking agent 2 comprises the following steps: (1) Add an appropriate amount of organic solvent (epichlorohydrin) and deionized water into a reaction vessel and stir at a rate of 350 r / min to mix them thoroughly; (2) Slowly add raw material A (ethylenediamine) and catalyst B (ammonium persulfate), stir and react at 60°C, add raw material C (acryloyloxyethyltrimethylammonium chloride) dropwise, raise the temperature to 90°C after the addition is complete, keep the temperature for reaction for 3 hours, and then cool to obtain a uniform liquid.

4. According to claim 1, a three-dimensional cross-linking sealing technology based on electrostatic force is characterized in that: The auxiliary agent is composed of an antibacterial agent dodecyl benzyl ammonium chloride (1227), a gel promoter disodium ethylenediaminetetraacetate (EDTA), and a regulator mainly composed of thiourea.

5. According to claim 1, a three-dimensional cross-linking sealing technology based on electrostatic force is characterized in that: The polymers include ultra-high-density (2500×104) salt-resistant polymers and high-density polymers (1600-1900×104).

6. According to claim 4, a three-dimensional cross-linking sealing technology based on electrostatic force is characterized in that: The concentration of the auxiliary agent is not higher than 800 mg / L and not lower than 400 mg / L.

7. According to claim 5, a three-dimensional cross-linking sealing technology based on electrostatic force is characterized in that: The polymer concentration is not higher than 4000 mg / L and not lower than 1000 mg / L.

8. According to claim 1, a three-dimensional cross-linking sealing technology based on electrostatic force is characterized in that: The concentration of the cross-linking agent is not higher than 5000 mg / L and not lower than 2000 mg / L.